COMPARISON OF PARAMETER LOGISTIC MODELS OF RAJU DIFFERENTIAL ITEM FUNCTIONING ITEM RESPONSE BASED - Oyeniran, Daniel (African Journal of Behavioural and Scale Development Research, 2024)
In educational and psychological assessment, item bias might result in an unfair advantage or disadvantage for some group. As a result, the statistical strategies for detecting DIF in the Raju model have been proposed. Most of these techniques are intended for comparing pre-defined focal and reference groups, such as males and females. A total of 480 students attempted 30 mathematics items from each of the five areas that have continuously been identified by West African Examination Council (WAEC) chief examiners for the past ten years as challenging for the student to acquire appreciable results from the items related to them. The Raju method of DIF was utilized, and because it is based on IRT, the 1PL, 2PL, and 3PL models were compared to determine which items bias male and female samples. The results demonstrate that when 1PL is employed, two items have DIF, however when 2PL and 3PL are utilized, 26 items are biased. As a result, it's clear that those topics aren't as difficult as they appear, but students aren't scoring well because of the bias in those items. Without considering the influence of DIF, it is reasonable to assume that only around half of the students performed well on these tasks. It is not because the pupils do not know the answer, but rather because the items are biased, making it difficult for them to perfect their response efficiently.